Protection Over current Curve plotter with Fault locator application - Sithole, Y; Kotze, B (24th Southern African Universities Power Engineering Conference, 26 - 28 January 2016, Vereeniging, South Africa, 2016)
The development of a software application to plot protection coordination curves and provide a distance to fault locator is presented in this paper. The purpose of the application is to aid fault location in power systems. Incorrect tripping of protection relay and fault location on power lines have a significant impact on power system performance. Often protection engineers and technicians need to verify grading of protection relays and to locate faults on power lines. The application developed will allow drawing of protection relay curves to observe coordination of relays. It also has a fault locator for non-homogenous medium voltage networks in distribution which estimates distance to fault given the network topology and measured fault current. The application was developed on Microsoft Excel® using the Visual Basic programming language. This will allow the application to be run on any device supporting Excel, originally planned to run on a smart phone, thus making the software easily accessible. The application allows up to four relay curves to be drawn with a variety of curve types to choose from. The fault locator allows up to four conductor types to be used in the network topology to accurately model the fault path. The fault locator was tested with data obtained from two medium voltage overhead lines and gave satisfactory results.
Published Conference Proceedings
Keywords: Protection; over current; curve plotter; fault locator; Excel; Visual Basic; medium voltage